Unique reactivity of an alpha-ketiminopyridine ligand with metal-alkyls: Synthesis and ROP of epsilon-caprolactone - Novák, Miroslav; Jambor, Roman; Růžičková, Zdeňka; Podzimek, Štěpán (Royal Society of Chemistry, 2021)
The reaction of an alpha-ketimininopyridine ligand 2-((Me)C = N(C6H3-2,6-iPr(2)))-6-(OMe)C5H3N (L-1) with metal-alkyls, such as MeLi, Et2Zn, Me3Al and Me2AlCl, was studied. The reaction of L-1 with MeLi led exclusively to the formation of [2-((H2C)C-N(C6H3-2,6-iPr(2)))-6-(OMe)C5H3N]Li center dot(THF)(2) (1 center dot(THF)(2)) with a deprotonated ketimine methyl group as a product of methane elimination. The treatment of L-1 with Et2Zn provided, at the first stage, only complex [2-((Me)C = N(C6H3-2,6-iPr(2)))-6-(OMe)C5H3N]ZnEt2 (2). The nonstability of 2 led to ethane elimination along with the deprotonation of a ketimine methyl group, which further yielded [2-((H2C)C-N(C6H3-2,6-iPr(2)))-6-(OMe)C5H3N]ZnEt (3). In contrast, Me3Al reacted with L-1 in a carboalumination fashion and [2-((Me)(2)C-N(C6H3-2,6-iPr(2)))-6-(OMe)C5H3N]AlMe2 (4) was isolated. In the case of Me2AlCl, an ionic species {[2-((Me)C = N(C6H3-2,6-iPr(2)))-6-(OMe)C5H3N]AlMe2}(+) {Me2AlCl2}(-) (5) was formed as a result of a spontaneous dissociation of Me2AlCl initiated by the ligand L-1. Since compounds 2-5 contain a metal-alkyl fragment, they were used as pre-catalysts in ROP of epsilon-caprolactone, as well as compound 1 center dot(THF)(2).
Unikátní reaktivita alfa-ketiminopyridinového ligandu s alkyl-kovy: Syntéza a ROP epsilon-kaprolaktonu
Keywords: epsilon-caprolactone; alpha-ketiminopyridine; alkyl-iron; alfa-ketiminopyridin; alkyl-kov; ring-opening polymerace; epsilon-kaprolakton